Pendidikan Pluralisme Agama: Kajian tentang Integrasi Budaya dan Agama dalam Menyelesaikan Konflik Sosial Kontemporer - Saihu Saihu (JURNAL INDO-ISLAMIKA, 2019)
This paper argues that culture is a part of religion in the sense that the latter (religion) authentically aims to help bless people as well to perpetuate peace among them. This article uses the term “culture” to refer to this perpetuated value. This action is in tandem with pluralism education; that is, an education that directs its students to free themselves up from any type of prejudice, and to be capable of not only learning knowledge in their classes, but also other cultures and perspectives available in the multicultural societies. Therefore, this pluralism education expects the students to qualify themselves with empathy, tolerance and solidarity to diverse groups of people in this world. Such a tremendous pluralism education occurs in Bali, Indonesia.